2016
DOI: 10.3389/fbuil.2016.00017
|View full text |Cite
|
Sign up to set email alerts
|

Shared Value Potential of Transporting Cargo via Hyperloop

Abstract: This research estimates the shared value created by constructing a hypothetical Hyperloop to transport cargo along 300 km in Northern Germany. Following Porter and Kramer (2011, 2012), we identified and evaluated eight factors that create shared value: travel speed, operating costs, safety, noise pollution, air pollution, climate effect/ carbon footprint, separation effect/property efficiency, and maintenance. Using official data compiled by several German institutes and organizations, we conducted comparative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Pipeline systems such as, for example, Hyperloop or Cargo Sous Terrain are being discussed as a new transport mode for goods-and/or passenger-transport (see, e.g., Markvica et al [17]). Hansen [18] and Werner et al [19] assess the deployment of the Hyperloop for passenger and goods transport in the pipeline. Stein and Schoesser [20] examine new technologies for urban goods transport and, therefore, focus on CargoCap, which poses a subterranean pipeline freight transport system.…”
Section: Pipelinesmentioning
confidence: 99%
“…Pipeline systems such as, for example, Hyperloop or Cargo Sous Terrain are being discussed as a new transport mode for goods-and/or passenger-transport (see, e.g., Markvica et al [17]). Hansen [18] and Werner et al [19] assess the deployment of the Hyperloop for passenger and goods transport in the pipeline. Stein and Schoesser [20] examine new technologies for urban goods transport and, therefore, focus on CargoCap, which poses a subterranean pipeline freight transport system.…”
Section: Pipelinesmentioning
confidence: 99%
“…In fact, the work addresses how Hyperloop technology can provide support in the freight transportation industry. Also, in the work of Werner et al (2016), the implementation of a 300 km long Hyperloop system in northern Germany for freight transport is analyzed. Specifically, the authors identified and evaluated eight elements: i) travel speed, ii) operational costs, iii) safety, iv) noise pollution, v) air pollution, vi) climate impact -carbon footprint, and vii) maintenance aspects.…”
Section: Introductionmentioning
confidence: 99%
“…Description of the hyperloop system components is provided in several studies [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Hyperloop studies focus on specific performance topics, such as aerodynamics [15,18,, safety [8,9,16,19,20,44,45], and energy [7,9,14,[16][17][18]23,28,39,44,[46][47][48][49][50][51][52][53][54][55][56][57][58], while others focus on different hyperloop technologies, such as in the field of pneumatic tube and tunnel systems…”
Section: Introductionmentioning
confidence: 99%